Bio-hydrogen production by oxidative steam reforming of biogas over nanocrystalline Ni/CeO2 catalysts. (21st September 2015) - Italiano, Cristina; Vita, Antonio; Fabiano, Concetto; Laganà, Massimo; Pino, Lidia
Abstract This study focuses on the synthesis of nanocrystalline Ni/CeO2 catalysts for the biogas oxy-steam-reforming (OSR) process. The solution combustion synthesis (SCS) has been studied varying the fuel (oxalyldihydrazide, urea, carbohydrazide) and the cerium precursor (cerium nitrate and ammonium cerium nitrate). The physical-chemical characterizations have shown that the morphological and redox properties of the prepared samples are strictly connected with the selection of precursors and fuel for the solution combustion mixture. Particularly, the use of urea as fuel allows to improve nickel dispersion, surface area and reducibility of the catalysts, affecting positively the OSR performances.